A survey of the experience of living with dementia in a dementia-friendly community. (July 2021) - Darlington, Nicole; Arthur, Antony; Woodward, Michael; Buckner, Stefanie; Killett, Anne; Lafortune, Louise; Mathie, Elspeth; Mayrhofer, Andrea; Thurman, John; Goodman, Claire
Dementia-friendly communities (DFCs) are one way in which people living with dementia can be supported to be active, engaged and valued citizens. Quantitative evaluations of the experiences of those with dementia living within these communities are scarce. This article reports findings from a survey of people living with dementia on their experience of living in a DFC. Two-hundred and forty people living with dementia completed a cross-sectional survey in six DFCs across England. Around half of respondents reported they were aware they were living in a DFC. Being aware of living in a DFC was associated with taking part in leisure activities ( p = 0.042), community centre attendance ( p = 0.009), being involved in organised activities or groups ( p < 0.001), feeling understood ( p = 0.008), and feeling valued for their own contributions to the community ( p = 0.002). This study illustrates the contribution that surveys can make in facilitating the expression of views and experiences of people living with dementia. Awareness of living within a DFC is associated with greater involvement in, and belonging to, the wider community.